1990
DOI: 10.1056/nejm199003223221205
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the 5-Hydroxytryptamine3(Serotonin) Antagonist Ondansetron (Gr 38032F) with High-Dose Metoclopramide in the Control of Cisplatin-Induced Emesis

Abstract: To compare ondansetron (GR 38032F), a 5-hydroxytryptamine3-receptor antagonist, with metoclopramide in the prophylaxis of acute cisplatin-induced emesis, we conducted a double-blind crossover study in 97 patients scheduled to receive cisplatin (80 to 100 mg per square meter of body-surface area) for treatment of cancer. None had received chemotherapy before this trial. Among the 76 patients who satisfactorily completed both parts of the study, complete or nearly complete control of emesis (i.e., no episodes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
108
1
3

Year Published

1992
1992
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(114 citation statements)
references
References 18 publications
2
108
1
3
Order By: Relevance
“…Comparative trials with high-dose metoclopramide have demonstrated that dolasetron, ondansetron, and granisetron are more effective in preventing acute emesis, are better tolerated, and are preferred by more patients [1,19,[48][49][50]. 5-HT 3 -receptor antagonists have become the agents of choice in preventing acute CINV following both moderately and highly emetogenic chemotherapy [11,51].…”
Section: Optimizing Efficacymentioning
confidence: 99%
“…Comparative trials with high-dose metoclopramide have demonstrated that dolasetron, ondansetron, and granisetron are more effective in preventing acute emesis, are better tolerated, and are preferred by more patients [1,19,[48][49][50]. 5-HT 3 -receptor antagonists have become the agents of choice in preventing acute CINV following both moderately and highly emetogenic chemotherapy [11,51].…”
Section: Optimizing Efficacymentioning
confidence: 99%
“…The prevention and treatment of these symptoms was greatly improved with the development of selective 5HT3-receptor antagonists, which control nausea and vomiting in more than 70% of cisplatin-treated patients in the first cycle of chemotherapy (Marty et al, 1990;de Mulder et al, 1990;Hainsworth et al, 1991). Anti-emetic protection against both acute and delayed emesis is improved further by the combined use of a 5HT3 antagonist plus dexamethasone (Roila et al, 1991;Smith et al, 1991;Ahn et al, 1994;Hesketh et al, 1994; Italian Group for Antiemetic Research, 1995).…”
mentioning
confidence: 99%
“…Until recently, even with the use of the most active antiemetic combination regimen (metoclopramide with lorazepam and dexamethasone), a considerable proportion of patients suffered from nausea and vomiting whereas the new 5HT3-antagonists are now found to be more effective in preventing acute nausea and vomiting induced by cisplatin (Cubbedu et al, 1990;Marty et al, 1990;Smith et al, 1990; de Mulder et al, 1990). …”
mentioning
confidence: 99%